The Airport Wildlife Control Unit Design as the Safety Measure - M. Rifqi Andika Wijaya; Dwi Lestary; Dini Wagini; Pangsa Rizkina Aswia (Institut Transportasi dan Logistik Trisakti, 2022)
Safety is the main goal that should be achieved in the aircraft operation activities. Birds and other wild animals could give a serious impact to the aircraft operation activities that could endanger the safety and secure activities of aviation. For this reason, wildlife hazard management is very important to reduce the impact. The goal of the wildlife hazard implementation is one of the efforts to secure the Airport Wildlife Control Unit by manipulating the animals’ behavior of their habitats. Based on the regulation of Director General of Air Transportation, Number: SKEP/42/III/2010 Advisory Circular CASR 139-03, the wildlife hazard management is in the area of airport. This research was done by conducting the needs assessment of stakeholder groups to find out the needs related to AWCU. After getting the data, the product design and validation were carried out by experts in the field of safety management system. The results are to form the AWCU and develop procedures to handle wild animals. The aim of the Research and Development is to describe the formation of the Airport Wildlife Control Unit by identifying potential danger of birds and wild animals attack, implementing the habitat management, by conducting birds and wild animals’ surveillance and coordinating with related units.